Child and adolescent development for educators - Meece, Judith L. (McGraw-Hill, 1997)
As the title suggests, this text is designed specifically for students preparing for teaching or other education-related careers. It is the only text to date that focuses entirely on the development of school-age children and youth and whose examples are taken entirely from schools and classrooms. Likewise, its topical coverage reflects the developmental concerns of real-life educators, that is, there is a heavy treatment of cognitive, language, and social-emotional development during the school years.
Keywords: Lehrbuch; Kind; Adolescence; Child development; Children; Cognition in children; Constructivism (Education); Heranwachsender; Entwicklungspsychologie; Entwicklung; Schulkind; Wortbildung; Gegenwartssprache; Deutsch